An Ethical Framework and Fundamental Challenges of New Medias in Present Scenario: Navigating ethical challenges in the era of new media (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Media is a monitor, source and communicative core of the society. In the middle of present advanced scenario there has been introduced a several various different new Medias under the particular program profile. In the basics of profile profit, targets, challenges and many more fundamental frame works play a structural role. Being a responsible profession still from the past, Medias have been followed the professional ethics. But as for the regional boundaries the Medias as well as new Medias ethical structures would be more or less differ. In this same way their risks, professional tasks and impact-able challenges are also moves together. For the seek of disclosing the dingers facts and figures along with relieve the hidden trough and solid findings knowingly or unknowingly the present new Medias have been committed for multi stage challenges with ethical restrictions’. Whatever, regarding with these circumstances till today the modernized new Medias have been introduced in huge numbers. As well it has been practiced in several service framework boundaries in micro to macro and unit to universal numerous mode in all over the world. Accordingly the present scenario the media is one of an advanced flat-form to introduce, share, spread as well as famous the issues in short movement.